Comparing patterns of sexual risk among adolescent and young women in a mixed‐method study in Tanzania: implications for adolescent participation in HIV prevention trials. Issue 3 (8th September 2014) - Tolley, Elizabeth E; Kaaya, Sylvia; Kaale, Anna; Minja, Anna; Bangapi, Doreen; Kalungura, Happy; Headley, Jennifer; Baumgartner, Joy Noel
Abstract : Introduction: Despite the disproportionate impact of HIV on women, and adolescents in particular, those below age 18 years are underrepresented in HIV prevention trials due to ethical, safety and logistical concerns. This study examined and compared the sexual risk contexts of adolescent women aged 15–17 to young adult women aged 18–21 to determine whether adolescents exhibited similar risk profiles and the implications for their inclusion in future trials. Methods: We conducted a two‐phase, mixed‐method study to assess the opportunities and challenges of recruiting and retaining adolescents (aged 15–17) versus young women (18–21) in Tanzania. Phase I, community formative research (CFR), used serial in‐depth interviews with 11 adolescent and 12 young adult women from a range of sexual risk contexts in preparation for a mock clinical trial (MCT). For Phase II, 135 HIV‐negative, non‐pregnant adolescents and young women were enrolled into a six‐month MCT to assess and compare differences in sexual and reproductive health (SRH) outcomes, including risky sexual behaviour, incident pregnancy, sexually transmitted infections (STIs), reproductive tract infections (RTIs) and HIV. Results: In both research phases, adolescents appeared to be at similar, if not higher, risk than their young adult counterparts. Adolescents reported earlier sexual debut, and similar numbers of lifetime partners, pregnancy and STI/RTI rates, yet had lower perceived risk. Married women in the CFR appeared at particular risk but were less represented in the MCT. In addition, adolescents were less likely than their older counterparts to have accessed HIV testing, obtained gynaecological exams or used protective technologies. Conclusions: Adolescent women under 18 are at risk of multiple negative SRH outcomes and they underuse preventive services. Their access to new technologies such as vaginal microbicides or pre‐exposure prophylaxis (PrEP) may similarly be compromised unless greater effort is made to include them in clinical trial research.